Transformational Leadership in Developing the Quality of Lecturers' Careers in Islamic Higher Education - Faqih, Moh Mahfudz; Najiburrohman, Najiburrohman; Hasanah, Maulidatul (Journal of Educational Management Research, 2025)
This research explores the role of ethics, morality, and intellectual stimulation in improving the quality of lecturers’ careers at a higher education institution grounded in Islamic values. The study focuses on how these factors contribute to developing lecturers’ academic and professional competencies while upholding Islamic principles. A qualitative approach was employed, utilizing interviews and observations with key university stakeholders, including rectors, deans, and lecturers, to gather insights into the institution’s practices and programs. The findings reveal that ethics and morality, particularly integrity, justice, and responsibility, are central to leadership practices and contribute to a harmonious academic environment. Intellectual stimulation, through training programs, workshops, and collaborative research, significantly enhances critical thinking and creativity among lecturers. Furthermore, a strong religious community fosters collaboration and supports career growth. The implications of this research suggest that integrating ethical values and intellectual engagement in academic environments can lead to more effective career development for lecturers, aligning with both professional growth and moral integrity. The study also highlights the need for future research to broaden the scope, incorporating diverse educational settings and gender perspectives to provide a more comprehensive understanding.